IL-10 inhibits CD28 and ICOS costimulations of T cells via src homology 2 domain-containing protein tyrosine phosphatase 1 - AKKOÇ, TUNÇ (MOSBY-ELSEVIER, 2007)
Background: Specific T-cell activation requires T-cell receptor stimulation and the generation of costimulatory signals. Major costimulatory signals are delivered to T cells by the interaction of CD28 and inducible costimulator (ICOS). Objective: To investigate the molecular pathways involved in direct T-cell suppression by IL-10. Methods: T-cell proliferation analysis, immunoprecipitations, and Western blots were performed after T-cell receptor and CD28 and ICOS stimulations in the absence or presence of IL-10. Dominant-negative src homology 2 domain-containing protein tyrosine phosphatase I (SHP-1) overexpression, small inhibitory RNA, and SHP-1-deficient and IL-10-deficient mice were used. Results: IL-10 receptor-associated tyrosine kinase Tyk-2 acts as a constitutive reservoir for SHP-1 in resting T cells, and then tyrosine phosphorylates SHP-1 on IL-10 binding. SHP-1 rapidly binds to CD28 and ICOS costimulatory receptors and dephosphorylates them within minutes. In consequence, the binding of phosphatidylinositol 3-kinase to either costimulatory receptor no longer occurs, and downstream signaling is inhibited. Accordingly, spleen cells from SHP-1-deficient mice showed increased proliferation with CD28 and ICOS stimulation in comparison with wild-type mice, which was not suppressed by IL-10. Generation of dominant-negative SHP-1-overexpressing T cells or silencing of the SHP-1 gene by small inhibitory RNA both altered SHP-1 functions and abolished the T-cell suppressive effect of IL-10. Conclusion: The rapid inhibition of the CD28 or ICOS costimulatory pathways by SHP-1 represents a novel mechanism for direct T-cell suppression by IL-10. Clinical implications: Molecular mechanisms of direct T-cell suppression by IL-10 may provide a novel target for therapy of allergy/asthma and autoimmune disease.
Keywords: IL-10; T cell; suppression; costimulation; anergy; SHP-1; phosphorylation; tolerance; inhibition; TYROSINE-PHOSPHATASE SHP-1; PHOSPHATIDYLINOSITOL 3-KINASE; IMMUNE-RESPONSES; REGULATORY CELLS; ACTIVATION; PROTEIN; BINDING; PHOSPHORYLATION; KINASE; MOTIF